Ultra-fast spinor switching in polariton condensates - Askitopoulos, Alexis (2017)
We demonstrate a linear to circular polarization conversion mechanism of a confined polariton condensate created by an optical potential trap. This system features a high degree of circular polarization under linear polarization pumping and is favorable for the development of spin logic operations. The physical mechanism behind this process is explained by the spin precession in the exciton reservoir that results in a condensate of a preferred spin state. Application of a non-resonant below threshold femtosecond pulse on the spinor condensate results in an ultrafast reversal of the spin state.